ANALYSIS OF RELATION BETWEEN PRESTATION INDEKS WITH NURSE JOB PERFORMANCE WHO GRADUATE FROM AKES RAJEKWESI BOJONEGORO - SUDALHAR, SUDALHAR (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2010)
The nurse job performance influenced by many factors, one of them is pretation indeks. Prestation indeks consits of general lecture, nursing basic lecture, and profesion lecture indeks. These are indicated their ability about nursing science. However there was no reseach about this.This reseach aim to know relation betweeen prestation indeks with nurse job performance. It has done in December 6 to 18 2008. Design of this reseacrh is cross sectional study, The population is all of alumny of Akes Rajekwesi Bojonegoro who get job in Bojonegoro Hospitals, Sumberjo hospital, Aisiyah hospital and Sumberjo Muhammadiyah hospital. These are 32 samples who choosed bay stratified random sampling. The data collected by quisioner and observation then analysed with SPSS Multiple Regretion with significan level p<0,05.The result shows there is relation betweeen comulative prestation index with nurse job performance especially nursing basic science and profesion science prestation index. It will recomended to choose nurse with higher prestation indek in nurse recruitmen